Modern architectural theory : a historical survey, 1673-1968 - Mallgrave, Harry Francis (Cambridge University Press, 2005)
Modern Architectural Theory is the first book to provide a comprehensive survey of architectural theorem, primarily in Europe and the United States, during three centuries of development. In this synthetic overview, Harry Mallgrave contextualizes architectural discourse within its social and political atmosphere.